Distribution of job satisfaction in different groups of employees in Chile: similarity with individualistic cultures - Raineri B., Andrés (Estudios de Administración, 2007)
Work satisfaction differences were analyzed between groups of Chilean employees as a function of their age and job level. Results showed that the older the employees the higher their worksatisfaction. Results also showed that the higher the hierarchical level of employees the higher was their work satisfaction. Chile has been described as having a collectivistic culture by several authors, but this positive relationship between hierarchical level and work satisfaction resembles findings from individualistic cultures which show a similar relation between these two variables. These results distance Chile from other collectivistic cultures, such as Asian cultures, where no differences in job satisfaction attributable to hierarchical level have been found. Consequences and possible explanations for these results are discussed.